The isolation, genetic characterisation and biological activity of a South African Phthorimaea operculella granulovirus (PhopGV-SA) for the control of the Potato Tuber Moth, Phthorimaea operculella (Zeller) - Jukes, Michael David (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
The potato tuber moth, Phthorimaea operculella (Zeller), is a major pest of potato crops worldwide causing significant damage to both field and stored tubers. The current control method in South Africa involves chemical insecticides, however, there is growing concern on the health and environmental risks of their use. The development of novel biopesticide based control methods may offer a potential solution for the future of insecticides. In this study a baculovirus was successfully isolated from a laboratory population of P. operculella. Transmission electron micrographs revealed granulovirus-like particles. DNA was extracted from recovered occlusion bodies and used for the PCR amplification of the lef-8, lef-9, granulin and egt genes. Sequence data was obtained and submitted to BLAST identifying the virus as a South African isolate of Phthorimaea operculella granulovirus (PhopGV-SA). Phylogenetic analysis of the lef-8, lef-9 and granulin amino acid sequences grouped the South African isolate with PhopGV-1346. Comparison of egt sequence data identified PhopGV-SA as a type II egt gene. A phylogenetic analysis of egt amino acid sequences grouped all type II genes, including PhopGV-SA, into a separate clade from types I, III, IV and V. These findings suggest that type II may represent the prototype structure for this gene with the evolution of types I, III and IV a result of large internal deletion events and subsequent divergence. PhopGV-SA was also shown to be genetically more similar to South American isolates (i.e. PhopGV-CHI or PhopGV-INDO) than it is to other African isolates, suggesting that the South African isolate originated from South America. Restriction endonuclease profiles of PhopGV-SA were similar to those of PhopGV-1346 and PhopGV-JLZ9f for the enzymes BamHI, HindIII, NruI and NdeI. A preliminary full genome sequence for PhopGV-SA was determined and compared to PhopGV-136 with some gene variation observed (i.e. odv-e66 and vp91/p95). The biological activity of PhopGV-SA against P. operculella neonate larvae was evaluated with an estimated LCâ‚…â‚€ of 1.87Ã—10â ¸ OBs.mlâ »Â¹ being determined. This study therefore reports the characterisation of a novel South African PhopGV isolate which could potentially be developed into a biopesticide for the control of P. operculella.
Keywords: Potato tuberworm; Potatoes -- Diseases and pests -- South Africa; Baculoviruses; Natural pesticides; Biological pest control agents; Potato tuberworm -- Biological control; Restriction enzymes, DNA